ECONOMIC CRISES AT THE ENTERPRISE: ENTITY, FEATURES AND FACTORS OF ORIGIN (Journal of Economic Research & Business Administration, 2017)
The purpose of the current research work is to suggest the mechanism of crisis management in the Republic of Kazakhstan. As every enterprise is vulnerable to crisis, the market has witnessed countless of examples that a small mistake or an unexpected weak changes, sometimes even a small incorrect business move from an enterprise under some certain circumstance might bring lethal result to the existing of the enterprise. And a lot of situations that can be threatening or could harm the enterprise by seriously interrupting business, significantly damaging image, and hampering the normal cash flow to trap the enterprise in an even worse dilemma of payment lack of monetary asset or bankruptcy. The joint adventure combines different culture and resources to contribute the improvement of crisis mechanism management in Kazakhstan.